An Experimental Murine Model to Study Acquisition Dynamics of Tick-Borne Langat Virus in Ixodes scapularis - Ahmed, Waqas; Rajendran, Kundave V.; Neelakanta, Girish; Sultana, Hameeda (Frontiers in Microbiology, 2022)
Ixodes scapularis ticks acquire several pathogens from reservoir animals and transmit them to humans. Development of an animal model to study acquisition/transmission dynamics of these pathogens into and from ticks, respectively, is challenging due to the fact that in nature ticks feed for a longer duration and on multiple vertebrate hosts. To understand the complex nature of pathogen acquisition/transmission, it is essential to set up a successful tick blood feeding method on a suitable vertebrate host. In this study, we provide evidence that murine model can be successfully used to study acquisition dynamics of Langat virus (LGTV), a member of tick-borne flaviviruses. Mice were inoculated intraperitoneally with LGTV that showed detectable viral loads in blood, skin and other tissues including brain. Both larval and nymphal ticks that were allowed to feed on murine host, successfully acquired LGTV loads. Also, we found that after molting LGTV was transstadially transmitted from larval to nymphal stage. In addition, we noted that, LGTV down-regulated IsSMase expression in all groups of ticks possibly for its survival in its vector host. Taken together, we provide an evidence on the use of murine model to not only study acquisition dynamics of LGTV but also to study changes in tick gene expression during acquisition of arboviruses into ticks.